Predictors of social responsibility of Malaysia adolescents - Baharudin, Rozumah; Zulkefly, Nor Sheereen; Yahya, Amira Najiha; Mohd. Kadri, Nur Syuhaida (Institut Penyelidikan Pembangunan Belia Malaysia, 2015)
This study is intended to identify social responsibility of adolescents from both urban and rural areas and their unique predictors. Sample comprised of 935 daily secondary schools adolescents ages between 16 to 17 years residing in the urban and rural areas in Kedah, Kelantan, Johor, Sabah, and Selangor. Data were collected using a self-administered questionnaire comprising several measures: Social Self-Efficacy Scale (Muris 2001), Inventory of Parent and Peer Attachment (Armsden and Greenberg 1987), a modified version (Afriani and Rozumah 2011) of Social and Personal Responsibility Scale (Conrad and Hedin 1981). Findings revealed that adolescents from rural areas have higher social responsibility than those from urban areas. Sex, social self-efficacy, and mother and peer attachments were predictive of social behavior of adolescents from both urban and rural adolescents. The study concludes that personal and family factors play significant roles in shaping adolescents’ social responsibility behavior. Findings imply that any efforts in cultivating social responsibility in adolescents should consider factors within the proximal context of the adolescents.